Application of the standard case definition in the case of Congo-Crimean Hemorrhagic Fever (CCHF) in the Zhambyl region of Kazakhstan - Andrey M Dmitrovskiy; Pak YeА; Syzdykov МS; Ryabushko YeA; Kamytbekova KZh; Iskakova FA (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
In the presented case, a typical example of CCHF is described, a patient who lives in an endemic territory and had risk factors for infection - cattle keeping and tick bite. The patient sought medical help in a timely mannert, but his diagnosis of CCHF was made late, due to underestimation of the risk factors for CCHF infection and non-use of the standard case definition. The correct diagnosis was made only after the appearance of the hemorrhagic syndrome. The appearance of bleeding in patients with CCHF presents a high risk of infection for others. But timely isolation and intensive treatment allowed for the prevention of infection of contact persons and save the patient's life.